Physical activity patterns among women during the postpartum period: an insight into the potential impact of perceived fatigue - Baian A. Baattaiah; Haya S. Zedan; Arwa S Almasaudi; Shoug Alashmali; Monira I. Aldhahi (BMC, 2022)
Abstract Background Regular participation in physical activity (PA) improves physical well-being and reduces the risk of contracting noncommunicable diseases. However, fatigue could negatively impact the PA participation of women in their postpartum period. This study delineated the levels of perceived fatigue and characterized the association between fatigue and the PA patterns of postpartum women. Methods A cross-sectional study was conducted using an online questionnaire distributed to postpartum women living in Saudi Arabia. Their perceived postpartum fatigue (PPF) was assessed using the fatigue severity scale; their PA, using the short form of the International Physical Activity Questionnaires; and their postpartum depression, using the Edinburgh Postnatal Depression Scale. Descriptive statistics were expressed as the mean ± standard deviation for normally distributed variables and as the median (interquartile range) for non-normally distributed variables. Between-group differences were tested using the Mann-Whitney U test for independent samples. To determine the relationship between the study variables, Spearman's rho correlation coefficient was calculated. Multiple linear regression analysis was performed to explain the role of fatigue severity as an independent predictor of the variance of the PA level. Results A total of 499 postpartum women were divided into the PPF group (43%), who self-reported fatigue, and the non-PPF group (57%), who self-reported no fatigue. There was a significant difference in the median of vigorous PA, and moderate PA which were significantly higher in the non-PPF group than in the PPF group. The women with PPF reported less engagement in walking and a longer sitting duration than the women without PPF. High fatigue severity was associated with lower moderate PA (β = -10.90; p = .005; R 2 = .21) and vigorous PA (β = -04; p < .001; R 2 = .13). These associations remained significant in the regression model after adjustment for the mother's depression score; age; number of children; body mass index (kg/m2); employment status; intake of vitamins B1 (thiamin), C, and D and of Omega-3; and walking metabolic equivalent. Conclusion PPF may reduce the PA of postpartum women. Strategies targeting PPF may buffer its harmful impacts, and thus, improve postpartum women's health.